PERILAKU POLITIK GEREJA KRISTEN EVANGELIS (GKE) DALAM PEMILIHAN UMUM LEGISLATIF DI KALIMANTAN TENGAH TAHUN 2019 - Sandi, Jhon Retei Alfri (Jurnal Politik Profetik, 2020)
Kalimantan Evangelical Church abbreviated as GKE is a Protestant church organization in Kalimantan. In political election, the potential of GKE is highly regarded as political ballot storage. The concurrent election of legislative and President in 2019 especially by the candidates for the parliament in Central Kalimantan pushed GKE into political attitudes and actions. How the political behavior of the GKE towards legislative candidates would like to be a big question in this discussion. Quantitative and qualitative research method was used to collect information or research data by involving a questionnaire technique that distributed online and in-depth interviews. The result shows that the GKE is not only involved to encourage congregations to use political rights and actively participated in the voting activities, but also actively encouraging the congregations through recommendation letter, promoting legislative candidates from GKE and mobilizing the potential of GKE resources to collect supports from the congregation.